Cointegration of Financial Literacy and Financial Behavior of Student Investment Decision Making - J H Wijaya; Febyana Rizki Dwiputeri; Dittia Avliliani; Ivan Gumilar Sambas Putra (Innovation Business Management and Accounting Journal, 2024)
This research was conducted to measure the impact of long-term influence between financial literacy and financial behaviour on student investment decisions. The sample in this study was 120 undergraduate Management students at Widyatama University. The data was collected by using a questionnaire and the sampling technique was using non-probability sampling with a more specific technique that was taken by the researcher in the non-probability sampling technique was purposive sampling. The total sample used in this study was 120 respondents. The method used is multiple linear regression analysis. The results showed that the independent variables, namely financial literacy and financial behaviour, had a long-term influence on the dependent variable, namely investment decisions. The findings suggest that enhancing financial literacy and promoting positive financial behaviors among students can lead to more informed and effective investment decisions in the long run. Consequently, universities and educational institutions should consider integrating comprehensive financial education programs into their curricula to better prepare students for future financial challenges and opportunities.